The Effectiveness of Individual Counseling on Preoperative Perceived Stress in Patients with Cholelitiasis Surgery - R Jalali; F Dehghan (Iran University of Medical Sciences, 2017)
Abstract Background & Aim: Tensions have become one of the main problems in societies. Studies of pre-surgery stress and anxiety have raised the attention of many researchers. The aim of this study was to determine the effect of individual counseling on perceived stress in patients before cholelithiasis surgery. Materials & Methods: In this quasi-experimental study, 40 pre-operative patients were selected by convenience sampling in Emam Reza Hospital (Kermanshah -2016). Then, they were assigned randomly to experimental (n=20) and control group (n=20). The intervention group received cognitive coping strategies but the control group received routine care. Data were collected by perceived stress scale and analyzed by descriptive statistics and analysis of covariance using SPSS software version 16. Results: After intervention, the mean of total perceived stress score in the experimental group (33.07 ± 9.22) was lower than that of the control group (39.33 ± 7.76), and the difference between mean and standard deviation of the data was significant at (P<0.05) level in the post-test. Conclusion: Based on the findings, individualized counseling was effective in reducing perceived stress in patients before surgery. Therefore, this approach can be used to reduce the perceived stress of patients before the surgery.